UPAYA ASEAN DALAM MENGATASI KASUS CYBERCRIME DI INDONESIA (2019-2021) - Ismail, Muhammad Rafizi; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study discusses ASEAN's efforts to overcome cybercrime cases in Indonesia. The issue of this crime resulted in losses for various parties including the state. Low security, low education, and low law enforcement are among the factors that encourage the issue of this crime to move freely. Efforts are being made to cooperate with ASEAN through ASEAN documents on transnational crime, as well as implementing cyber security, cyber resilience, and cyber diplomacy. This research uses qualitative methods, using case study research techniques through indirect sources such as notes, reports, articles or journals. This research uses the perspective of Neorealism, Cyber Security theory. The result of this paper is that ASEAN's efforts are still ongoing but Indonesia's support is also needed so that the implementation of security, resilience and diplomacy can be carried out properly. Keywords: ASEAN, Cybercrime, Cyber Diplomacy, Cyber Security, Cyber Resilience